High Impact at Low Cost: Initiating a Citation Analysis Program. Issue 4 (2nd October 2022) - Murphy, Greg; Plann-Curley, Brendan; Bilello, Kristina
ABSTRACT: University faculty under consideration for tenure and promotion are expected to demonstrate to their committees the value of their scholarly output. This case study involves the creation of a citation analysis service at a midsized university and reviews many of the existing sources for metrics and journal rankings – both subscription-based and freely available. The aim is to offer a roadmap for budget-minded academic libraries that want to assist their faculty in compiling individualized portfolios that include bibliometrics. Many existing tools favor the hard science fields. This case study focuses on a pathway through the confusing subject of citation analysis with a focus on the social sciences and humanities while highlighting the benefits for academic institutions and libraries.